PENERAPAN PENDEKATAN KONTEKSTUAL DALAM PEMBELAJARAN IPA DI SEKOLAH DASAR - Syamsu Arlis (Pedagogi: Jurnal Ilmu Pendidikan, 2013)
The contextual science learning strategy can be carried out to the optimum if supported by teachers” creativity and capability to make use of the students, their school, and its environment. The problem is whether teachers of students, learning science already have the capability to develop and implement a contextual learning strategy in their student. This paper is written for the purpose of increasing those teachers” knowledge and understanding of the aforesaid learning strategy in ordr that they can develop and to implement bit in their science classes. Being contextual, it is a strategy relating instructional content with real situations of the leaners and encouraging them to relate academic knowledge to its application in their lives as individuals and family or community members. Contextual learning has the following characteristics: 1) emphasizing problem solving, 2) recognizing that teaching and learning need to occur in multiple context, 3) assisting students in learning hoe to monitor their learning so that they become self-regulated learners, 4) anchoring teach ing in the diverse life context of students, 5) encouraging students to learn from from each other, and. 6) employing authentic assessment.